Vegetation and edaphic factors influence rapid establishment of distinct fungal communities on former coal-spoil sites. (June 2018) - Detheridge, Andrew Paul; Comont, David; Callaghan, Tony Martin; Bussell, Jennifer; Brand, Graham; Gwynn-Jones, Dylan; Scullion, John; Griffith, Gareth Wyn
Abstract: We investigated re-establishment of fungal communities on eight former colliery sites in South Wales following revegetation 22–27 y earlier. Regraded bare coal-spoil was seeded to sheep-grazed grasslands, with saplings planted into coal-spoil for woodlands. Metabarcoding (28S rRNA, D1 region) of soil fungal populations showed that woodland and grassland habitats were clearly divergent but edaphic variables only weakly affected fungal community structure. Root-associated basidiomycetes dominated all habitats, with ectomycorrhizal fungi more abundant in woodlands and Clavariaceae/Hygrophoraceae ('CHEG' fungi) in grasslands. The composition of coal-spoil grassland communities resembled that of a typical upland grassland site, suggesting that propagule immigration was not a limiting factor. However, fungal biomass (ergosterol) was 3-fold lower, reflecting high bulk density and poor structure. Re-establishment of fungal communities in coal-spoil soils represents an important barometer of restoration success. From a fungal conservation perspective, such sites represent important refugia for waxcap fungi subject to habitat loss from agricultural intensification.